2019
DOI: 10.1038/s41598-019-40500-1
|View full text |Cite
|
Sign up to set email alerts
|

Limits of Babinet’s principle for solid and hollow plasmonic antennas

Abstract: We present an experimental and theoretical study of Babinet’s principle of complementarity in plasmonics. We have used spatially-resolved electron energy loss spectroscopy and cathodoluminescence to investigate electromagnetic response of elementary plasmonic antenna: gold discs and complementary disc-shaped apertures in a gold layer. We have also calculated their response to the plane wave illumination. While the qualitative validity of Babinet’s principle has been confirmed, quantitative differences have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…However, the distribution of the delocalized field (e.g., electric for bowtie and magnetic for diabolo) differs. In general, magnetic fields are weaker than electric fields in agreement with previous findings [42,46].…”
Section: A Plasmonic Antennas Modes and Hot Spotssupporting
confidence: 92%
See 3 more Smart Citations
“…However, the distribution of the delocalized field (e.g., electric for bowtie and magnetic for diabolo) differs. In general, magnetic fields are weaker than electric fields in agreement with previous findings [42,46].…”
Section: A Plasmonic Antennas Modes and Hot Spotssupporting
confidence: 92%
“…The peak energies of the scattering efficiency in the complementary PA (i.e., bowtie and inverted bowtie, diabolo and inverted diabolo) of the same size differ by less than 11%. The difference is less pronounced for large antennas, in line with the requirements of Babinet's principle: perfectly thin and opaque metal [42]. For the bowtie geometry, the scattering peaks of inverted PAs are less intense and redshifted with respect to direct PAs (as is the case also for disc-shaped antennas [42]), while opposite is true for the diabolo geometry.…”
Section: A Plasmonic Antennas Modes and Hot Spotsmentioning
confidence: 72%
See 2 more Smart Citations
“…Babinet inverted plasmonic metasurfaces were used to produce spin-selective second-harmonic vortex beams [35]. It was shown that disks and cylindrical apertures differ quantitatively with respect to the Babinet complementarity because the apertures produce higher magnetic-to-electric-field ratios and better charge-transfer properties [36]. Miniarrays of elliptical nanoholes that are not superimposable on their mirror image exhibit chiroptical effects, i.e., selective reflection of a single spin state while preserving its handedness [37].…”
Section: Introductionmentioning
confidence: 99%